Proses Berpikir Kreatif Siswa dalam Pemecahan Masalah Kolaboratif pada Konteks Open Ended - Kharisma Normala Dewi; Tatag Yuli Eko Siswono (MATHEdunesa, 2026)
In 21st-century learning, creative thinking and collaboration skills are abilities that need to be developed in every subject, including mathematics. The low level of creative thinking skills among Indonesian students, as shown in the PISA results, as well as students' difficulties in individual problem solving, are important reasons for exploring the collaborative creative thinking process. Therefore, this study uses open-ended questions because this type of question allows for a variety of solution strategies and ideas to emerge, exposing students' creative thinking processes in a collaborative context. This study aims to describe students' creative thinking processes in collaborative problem solving in heterogeneous groups (high, medium, and low). This research is a descriptive qualitative study with two groups of eighth-grade students at a junior high school in Gresik as subjects. Data collection techniques included tests, observations, and interviews. Data analysis was conducted based on the stages of creative thinking according to Siswono (2008) and collaboration competencies according to the OECD (2017). The results showed that Group 1 demonstrated collaboration through active communication, role-sharing, and contributions from all members. This group successfully met all indicators of creative thinking, such as fluency, flexibility, and originality. In contrast, Group 2 was dominated by high-ability students in the early stages, while other members tended to be passive. Although participation increased during the planning phase of idea implementation, this group could only meet the fluency and flexibility indicators. The creative thinking process of both groups went through the stages of synthesizing ideas, developing ideas, planning idea implementation, and implementing ideas. Interaction patterns showed that high-ability students tended to lead, moderate-ability students acted as connectors, and low-ability students were passive but still contributed to task execution.